(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article analyzes the role of the divergent thinking approach in the formation of the concept of fractions in primary school students. Divergent thinking is the ability to look at a problem from different angles and propose several solutions. This approach, which provides a deep and correct understanding of the concept of fractions, allows students to imagine fractions in different ways, compare them, find equivalent fractions, and apply them in different models and contexts. The article explains with practical examples how this approach can be applied in the educational process.